2022
DOI: 10.5187/jast.2022.e8
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives and advances in probiotics and the gut microbiome in companion animals

Abstract: Competing interestsNo potential conflict of interest relevant to this article was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 130 publications
(236 reference statements)
1
14
0
Order By: Relevance
“…Bacteroidetes and Firmicutes were detected, which are the bacteria that make up the majority of human and animal gut microbiota. 30,31) Acidobacteria, Nitrospirae, and Verrucomicrobia were also detected in all the wells. After the sewerage works (see above), the pH became alkaline in well N1 (samples N1 0922, N1 1015, and N1 1221).…”
Section: Physicochemical Characteristics Of Well Water and Bacterial ...mentioning
confidence: 89%
“…Bacteroidetes and Firmicutes were detected, which are the bacteria that make up the majority of human and animal gut microbiota. 30,31) Acidobacteria, Nitrospirae, and Verrucomicrobia were also detected in all the wells. After the sewerage works (see above), the pH became alkaline in well N1 (samples N1 0922, N1 1015, and N1 1221).…”
Section: Physicochemical Characteristics Of Well Water and Bacterial ...mentioning
confidence: 89%
“…The previous investigation by Evivie et al [ 40 ] confirmed the medicinal usage of L. delbrueckii isolates as a probiotic against foodborne pathogens. Moreover, recent studies have evidenced the role of E. faecium as a promising probiotic candidate for both human and animal use [ 41 , 42 , 43 , 44 ]. Despite 16S rRNA being a very conserved region, six of our isolates revealed huge divergence in that region and this could be explained by the effect of environmental, demographic, genetic factors, and the maternal lifestyle on modifying the microbial diversity of human milk and infants’ gut [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are highly recommended to help alleviate gut-related symptoms like nausea and abdominal pain and increase gut microbial diversity [74]. In addition, the consumption of probiotics can help prevent severe COVID-19 clinical manifestations primarily related to the digestive tract [75].…”
Section: Therapies In the Management Of Gut-related Symptoms In Covid...mentioning
confidence: 99%